2019
DOI: 10.1111/ppl.13020
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hydrogen peroxide and sodium nitroprusside following chemical priming of Ocimum basilicum L. against salt stress

Abstract: Sodium nitroprusside (SNP) and hydrogen peroxide (H2O2), as priming agents, have the well‐recorded property to increase plant tolerance against a range of different abiotic stresses such as salinity. In this regard, the present study was conducted to evaluate the effect of different levels of SNP (100 and 200 µM) and H2O2 (2.5 and 5 mM) as well as their combinations under salt stress (0 and 50 mM NaCl) on key physiological and biochemical attributes of the economically important aromatic plant basil (Ocimum ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 58 publications
5
25
1
Order By: Relevance
“…Several studies showed that ROS are essential for the success of numerous fundamental natural processes, including cellular proliferation and differentiation [ 11 ]. In addition, H 2 O 2 is a critical component of stress response regulation in crop plants such as rice [ 13 ], wheat [ 14 ], maize [ 15 ], mung bean [ 16 ], soybean [ 17 ], cucumber [ 18 ], sour orange [ 19 ], strawberry [ 20 ], basil [ 21 ], and rapeseed [ 22 ]. Moreover, it is established that in addition to ROS, reactive nitrogen species (RNS), reactive sulfur species (RSS), and reactive carbonyl species (RCS) also play a key signaling role and are all involved in a cross-talk in plant abiotic stress tolerance [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that ROS are essential for the success of numerous fundamental natural processes, including cellular proliferation and differentiation [ 11 ]. In addition, H 2 O 2 is a critical component of stress response regulation in crop plants such as rice [ 13 ], wheat [ 14 ], maize [ 15 ], mung bean [ 16 ], soybean [ 17 ], cucumber [ 18 ], sour orange [ 19 ], strawberry [ 20 ], basil [ 21 ], and rapeseed [ 22 ]. Moreover, it is established that in addition to ROS, reactive nitrogen species (RNS), reactive sulfur species (RSS), and reactive carbonyl species (RCS) also play a key signaling role and are all involved in a cross-talk in plant abiotic stress tolerance [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kushwaha and Singh (2019) and Ahmad et al (2019) have reported various mechanisms through which H 2 S regulates chromium toxicity in crop plants. Regulatory roles of NO and H 2 S were reported for salt and drought stress, as well as iron deficiency in plants (Batista et al 2019, Gohari et al 2019, Jahan et al 2019, Kaya et al 2019a). The role of NO and H 2 S along with that of Si was evaluated for the regulation of cadmium stress in plants (Kaya et al 2019b).…”
mentioning
confidence: 99%
“…It is accepted that NO has basic and essential role in root development and also under stress conditions (Corpas and Barroso, 2015). NO can interact with other signal compounds, like hydrogen peroxide or hydrogen sulfide, which are also able to produce endogenously (Corpas et al, 2019;Gohari et al, 2020;Singh et al, 2020). NO could mediate auxin accumulation and signaling in Arabidopsis and decrease the size of root meristem size during salt stress (Liu et al, 2015).…”
Section: Potential Secondary Messengers Involved In Halotropism Seconmentioning
confidence: 99%
“…Stress factors usually occur combined combination to each other affecting RSA (Osthoff et al, 2019;Sewelam et al, 2020). There is an increasing evidence about significance of root tropism in adjusting root system to changing conditions due to global climate change and inadequate agricultural procedures (Rozema and Schat, 2013;Gohari et al, 2020;Zhao et al, 2020). Halotropism can help roots to navigate and remodel their system architecture by cost effective energy supply in order to successfully survive during different salt conditions.…”
Section: Potential Application Of Halotropism In Agriculture and Othementioning
confidence: 99%